ANALISIS KUALITAS SISTEM, KUALITAS INFORMASI DAN KUALITAS LAYANAN TERHADAP KEPUASAN PENGGUNA PADA SISTEM APLIKASI KEUANGAN TINGKAT INSTANSI SATUAN KERJA - Irma Hartiwi, Lorenzia Ida Ayu; Rokhayati, Hijroh (Jurnal Manajemen, 2023)
Agency Level Accounting System (SAKTI) is a product of the Ministry of Finance that was developed to comply with IFMIS's requirements. This study aims to analyze Individual perceptions related to system quality, information quality, service quality, and net benefit on user satisfaction for users of the SAKTI rollout application within the scope of the Office of the Ministry of Religion, Banyumas Regency. Using a questionnaire and purposive sampling, a study was conducted on sixty respondents. This study indicates that a quality system has no effect on the satisfaction user, meanwhile, quality information and quality service are influential positive on the satisfaction user. Moreover, systems quality, information quality, and service quality have no effect on net benefits. Whereas satisfaction users have a positive effect on net benefit.